Current status of postoperative infections after digestive surgery in Japan: The Japan Postoperative Infectious Complications Survey in 2015. Issue 3 (12th March 2019) - Niitsuma, Toru; Kusachi, Shinya; Takesue, Yoshio; Mikamo, Hiroshige; Asai, Koji; Watanabe, Manabu
Abstract: Aim: To survey postoperative infections (PI) after digestive surgery. Methods: This survey, conducted by the Japan Society of Surgical Infection, included patients undergoing digestive surgery at 28 centers between September 2015 and March 2016. Data collected included patient background characteristics, type of surgery, contamination status, and type of PI, including surgical site infection (SSI), remote infection (RI), and antimicrobial‐resistant (AMR) bacterial infections and colonization. Results: Postoperative infections occurred in 10.7% of 6582 patients who underwent digestive surgery (6.8% for endoscopic surgery and 18.7% for open surgery). SSI and RI, including respiratory tract infection, urinary tract infection, antibiotic‐associated diarrhea, drain infection, and catheter‐related bloodstream infection, occurred in 8.9% and 3.7% of patients, respectively. Among all PI, 13.2% were overlapping infections. The most common overlapping infections were incisional and organ/space SSI, which occurred in 4.2% of patients. AMR bacterial infections occurred in 1.2% of patients after digestive surgery and comprised 11.5% of all PI. Rate of AMR bacterial colonization after digestive surgery was only 0.3%. Conclusion: Periodic surveillance of PI, including AMR bacteria, is necessary for a detailed evaluation of nosocomial infections. Abstract : This survey by the Japan Society of Surgical Infection included patients undergoing digestive surgery at 28 centers between September 2015 and March 2016. Data collected included patient background characteristics, type of surgery, contamination status, type of postoperative infection including surgical site infection, remote infection, and antimicrobial‐resistant (AMR) bacterial infections as well as AMR bacterial colonization.